Design Thinking Implementation by Faculty through EPICS Project - Yakub, B.; Naik, Santosh Madeva; Unnisa, Azeem (Journal of Engineering Education Transformations, 2018)
In Today’s scenario, all the instructor are trying to mould themselves to engage students in learning through doing engineering than just studying engineering to meet the need of the 21st century learners. In this paper, EPICS initiative implementation which promotes doing engineering is being described and also focused on describing the training which team instructor had gone through and what learning’s & experiences were gained are explained briefly. The results showed that Instructors enjoyed the training and had lot of learning as they were working with real community partner for whom they developed and delivered the product as per the problem identified using design thinking process. This type of learning experiences can be improved by using better resources and significant time for doing project as the training described in this paper was short duration. The goal of this paper is to identify need of the old age people in terms of support to bare the capacity of weight of a person by depending on table while having food and medicine. The table should have Strong and convenient one. The table should enough to sustain the weight of the old people while having food and medicine. The table should have a ortability based on old age people requirement.